Data on dose-dependent cytotoxicity of rotenone and neuroprotection conferred by Yashtimadhu (Glycyrrhiza glabra L.) in an in vitro Parkinson's disease model - Gayathree Karthikkeyan (Elsevier, 2021)
The data described in this article presents the toxicity of rotenone and the neuroprotective effect of Yashtimadhu choorna (powder) in an in vitro Parkinson's disease model [1]. Yashtimadhu choorna is prepared from the roots of Glycyrrhiza glabra L., commonly known as licorice/ liquorice. The effects of rotenone and Yashtimadhu was assessed using cellular and molecular assays such as cell cytotoxicity assay, live-dead cell staining assay, cell cycle analysis, and western blotting. Protein-protein interaction was studied using ANAT plug-in in Cytoscape. Rotenone displayed time and dose-dependent toxicity, as evidenced by cell cytotoxicity assay and live-dead cell staining assay. Yashtimadhu showed no toxicity and prevented rotenone-induced toxicity. Rotenone and Yashtimadhu displayed differential control on the cell cycle. The Protein-interaction network showed the proteins interacting with ERK-1/2 and the pathways regulated by these interactions. The pathways regulated were primarily involved in cellular oxidative stress and apoptosis response. The data described here will enable the extent of cellular toxicity as a result of rotenone treatment and the neuroprotection conferred by Yashtimadhu choorna. This will enable understanding and exploring the effect of traditional and complementary medicine and aiding the identification of molecular targets to confer neuroprotection in Parkinson's disease.